Icelandic Immigrants and First Nations People in Canada - Sigrún B. Gunnarsdóttir 1954- (2010)
In this essay I will examine the first contact between the Icelandic immigrants who settled the western shore of Lake Winnipeg in Manitoba in the late nineteenth century and the local Natives. I will discuss in detail various sources found among personal letters and diaries of Icelandic settlers. I will examine the story of these two groups during these first years of Icelandic settlement and go from the more “official” documentation of the Icelandic Immigrant Saga to its more personal and often different version. In many of the books that have been published about the experiment of establishing an Icelandic colony in Canada, not much has been written about the Natives. The main purpose of my work is to delve into these personal sources and get a more explicit view of how these two peoples experienced each other, and if these relations were friendly and profitable for one groups or not. First, a short history about the local First Nations and the story of the Icelandic settlers is summarized. Narratives of Icelandic-Canadians are introduced which contain stories about the Natives. Immigrant Icelandic-Canadians poetry and contemporary work of Icelandic-Canadians authors involving the Natives are discussed. The story of the Native, John Ramsay, is introduced as well as the story of Helgi Einarsson. These two men were of great importance to the Icelandic-Canadian history. Interracial relationships also discussed. My conclusion is that these relations were most often friendly and beneficial for both groups. However, the Icelanders had to choose between having a good relationship with the Natives and being accepted as proper citizens by their host country. Despite this fact, a good affiliation survived between many of the Natives and the Icelandic-Canadians, and overcame this wall of ethnic separation. This proves that people of different races can build a common ground of communication if they so wish. Ritgerðin er lokuð til 31. október 2011.